A packet-based dual-rate PID control strategy for a slow-rate sensing Networked Control System. (May 2018) - Cuenca, A.; Alcaina, J.; Salt, J.; Casanova, V.; Pizá, R.
Abstract: This paper introduces a packet-based dual-rate control strategy to face time-varying network-induced delays, packet dropouts and packet disorder in a Networked Control System. Slow-rate sensing enables to achieve energy saving and to avoid packet disorder. Fast-rate actuation makes reaching the desired control performance possible. The dual-rate PID controller is split into two parts: a slow-rate PI controller located at the remote side (with no permanent communication to the plant) and a fast-rate PD controller located at the local side. The remote side also includes a prediction stage in order to generate the packet of future, estimated slow-rate control actions. These actions are sent to the local side and converted to fast-rate ones to be used when a packet does not arrive at this side due to the network-induced delay or due to occurring dropouts. The proposed control solution is able to approximately reach the nominal (no-delay, no-dropout) performance despite the existence of time-varying delays and packet dropouts. Control system stability is ensured in terms of probabilistic Linear Matrix Inequalities (LMIs). Via real-time control for a Cartesian robot, results clearly reveal the superiority of the control solution compared to a previous proposal by authors. Highlights: Implementation of a packet-based dual-rate control strategy to face time-varying delays, and packet dropout and disorder in a NCS Introduction of a prediction stage at the remote side, which contains a state resetting procedure, useful for unstable plants. Communication between controller and plant through a real shared medium: UDP communication. Facing time-varying delays and 30% of packet loses without significant degradation of the performance. Control system stability is ensured in terms of probabilistic Linear Matrix Inequalities (LMIs).